Legal Implications of Mining Corporate Social Responsibility Implementation in East Kalimantan Local Community Empowerment - Saputri, Novia Ardana; Yulianingrum, Aullia Vivi; Prasetyo, Bayu (Fakultas Hukum Universitas Islam Jakarta, 2024)
A form of responsibility that can be taken to reduce the impact of the mining business is implementing a Corporate Social Responsibility (CSR) program. This study aims to analyze the legal implications of implementing the social responsibility of mining companies in empowering local communities in East Kalimantan. The research method used is normative juridical, implementing the Limited Liability Company Law, which regulates CSR using a historical and comparative approach. The results show that CSR is a program that must be implemented by companies operating in the field and/or related to natural resources under the Law concerning Limited Liability Companies. CSR programs to empower local communities must be implemented under applicable principles, namely sustainability, accountability, and transparency. In conclusion, based on the findings, the implementation of this program has been carried out properly in accordance with the applicable principles and regulations by several mining companies in East Kalimantan. The East Kalimantan Provincial Government has implemented a Clean and Clear program for mining companies that do not implement CSR.